Pengaruh Supervisi Akademik Kepala Sekolah Berbasis Coaching dan Komunitas Belajar Terhadap Kompetensi Pedagogik Guru di Kecamatan Todanan - Any Inti Wahyu Setyaningrum; Soedjono Soedjono; Harto Nuroso (Jayapangus Press, 2026)
This study aims to examine and analyze the influence of coaching-based academic supervision of school principals and learning communities, both partially and simultaneously, on teachers' pedagogical competence. Previous research has generally focused on the influence of either principals' academic supervision or teacher learning communities separately on improving pedagogical competence. However, there has been little research that has comprehensively examined the influence of coaching-based academic supervision of school principals and teacher learning communities on teachers' pedagogical competence, particularly at the elementary school level in Todanan District, Blora Regency. This situation indicates a research gap that requires further study. The population is 308 people, the sample is 174 people. The instrument tests used are validity and reliability tests. The classical assumption test uses normality tests, linearity tests, multicollinearity tests, and heteroscedasticity tests. Data analysis uses multiple linear regression tests, F tests (ANOVA) and t tests. Based on the results of the study, it can be concluded as follows: (1) Coaching-based principal academic supervision has a positive and significant effect on teacher pedagogical competence. This is based on the results of a positive t-test, proven by the calculated t1 result of 8.241 > t table (α = 0.05, two tail) 1.974 and the significance level of the calculated t1 0.000 < 0.05; (2) The Learning Community has a positive and significant effect on Teacher Pedagogical Competence. This is based on the results of a positive t-test, proven by the calculated t2 result of 25.385 > t table 1.974; (3) The influence of the principal's academic supervision based on coaching and the Learning Community simultaneously has a positive and significant effect on Teacher Pedagogical Competence. This is based on the results of a positive F-test, proven by the calculated F value > F table (327.878 > 3.05)